2015
DOI: 10.1002/mats.201500031
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Microstructures Self‐Assembled from Linear Multiblock Copolymers in Thin Films

Abstract: Hierarchical lamellae self-assembled from linear multiblock copolymers in thin films are investigated by self-consistent field theory. The thin films are confined between two parallel substrates. The confinement strategy allows generating hierarchical microstructures with various numbers and different orientations of small-length-scale lamellae. Effects of film thickness and surface affinity on the structures are studied. It is found that not only the period of the large-and small-length-scale lamellae but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…In addition to the configuration entropy, conformation entropy and enthalpy effect are crucial to the phase behavior. By capturing these effects, researchers study the formation mechanism of hierarchical lamellae by using Self‐Consistent Field Theory (SCFT) . Besides SCFT, strong‐segregation theory (SST) and dissipative particle dynamics (DPD) were extensively used to study the phase behavior of a number of linear multiblock copolymers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the configuration entropy, conformation entropy and enthalpy effect are crucial to the phase behavior. By capturing these effects, researchers study the formation mechanism of hierarchical lamellae by using Self‐Consistent Field Theory (SCFT) . Besides SCFT, strong‐segregation theory (SST) and dissipative particle dynamics (DPD) were extensively used to study the phase behavior of a number of linear multiblock copolymers .…”
Section: Introductionmentioning
confidence: 99%
“…Besides SCFT, strong‐segregation theory (SST) and dissipative particle dynamics (DPD) were extensively used to study the phase behavior of a number of linear multiblock copolymers . Interestingly, by exhibiting the dynamics process of the formation of hierarchical structures, the small‐length‐scale nanostructures was found to form behind large‐length‐scale nanostructures, which shows great guidance for the controllable formation of the hierarchical morphologies …”
Section: Introductionmentioning
confidence: 99%
“…The calculation process of MD is more complicated and takes longer time. Therefore, for large molecular weight systems such as polymers, the coarse‐grained model is advantageous for reducing calculation time, and thus it is widely used in complex systems like polymer self‐assembly . The coarse‐grained model of DPD is dividing several atoms or groups into one bead.…”
Section: Methodsmentioning
confidence: 99%
“…Combining the effect of the enthalpy, Li and Shi studied the formation of LL structures and found that low IS interaction and high PI and PS interactions favor the formation of LL with more mid‐thin layers. [ 19 ] In addition to the LL nanostructure, cylinders‐in‐lamellae, lamellae‐in‐lamella , cylinders‐in‐ cylinder , and spheres‐in‐sphere, were also reported both in theory [ 20–30 ] and experiment. [ 31–34 ] Importantly, a series of multicontinuous network structures with controllable channels, including multicontinuous gyroid and O 70 network morphologies were obtained by using an effective design principle.…”
Section: Introductionmentioning
confidence: 99%